Abilities and limitations of a radar RASS wind profiler for the measurement of momentum flux in the planetary boundary layer - Lutz Hirsch; Gerhard Peters (Meteorologische Zeitschrift, 1998)
A radar wind profiler was used in the RASS mode to obtain remote measurements of the vertical flux of momentum. Time series of half-hour averaged values of the momentum flux are presented as well as profiles of multiple-hour averages recorded on convective summer days. The gross structure of the diurnal variation is in agreement with the expected behaviour of a convective boundary layer. Comparisons with in situ surface measurements using a sonic anemometer show a similar diurnal cycle but the amplitude of the surface momentum flux (6 m agl) is consistently smaller than in the lowest radar range gate (75 m agl). At higher altitudes the momentum flux amplitude decreases in reasonable agreement with the expected structure in a neutral or unstable boundary layer. In the night time (stable boundary layer) the flux - and consequently the flux gradient - vanishes in all heights including on the surface. The temporal structure of the radar measurements show less continuity than the surface data which is assumed to be caused by the "sampling problem" as the flux aloft is determined by few large eddies crossing the measuring volume during the averaging interval. But some contribution to the observed noise is artificial and related to the measuring principle. Possible improvements, to be expected by advanced radar techniques, are suggested in the concluding remarks.